Economic Impacts of the Florida Citrus Industry in 2003-04 - Alan Hodges; Mohammad Rahmani; David Mulkey (EDIS)
The citrus industry remains a major part of Florida's agricultural and natural resource economy. However, recently it has been adversely affected by hurricanes and diseases such as citrus canker and citrus greening. This paper presents estimates of the total impacts of the Florida citrus industry on the state's economy based on production values for the 2003-2004 crop year. Estimates are presented separately for fresh market citrus fruit and for processed juices and other byproducts. Impacts are expressed in terms of output, value added, employment, labor income, and indirect business taxes. This is EDIS document FE633, a publication of the Food and Resource Economics Department, UF/IFAS Extension. Published April 2006.